Direct assessment of upper limb muscle activity associated with dairy milking tasks through use of surface electromyography: an occupational research project - Mixco, Anthony, author; Rosecrance, John, advisor; Gilkey, David, advisor; Reiser, Raoul F., II, committee member; Tracy, Brian, committee member; Brazile, William, committee member (Colorado State University. Libraries, 2016)
Work-related musculoskeletal disorders (WRMSDs) are an economic burden on employers across all industries. Within agriculture, a high prevalence of WRMSDs have been found among dairy workers (specifically those involved in milking tasks) in small and large-herd operations. However, the effects of milking activities in large-herd dairy operations have not been investigated with the direct physical exposure measures, such as surface electromyography (sEMG), necessary to best quantify occupational risk. The goal of the research reported in this dissertation was to fill that gap, using sEMG to better quantify upper-limb muscle activity among large-herd dairy workers and to compare the muscle activity across large and small-herd operations. Three studies were conducted to reach this goal. In the first, sEMG was used to detail activity of upper-limb muscles across all milking tasks in large-heard dairies. This study revealed that the biceps brachii have the most activity in overall milking work. In the second study, sEMG was used to examine the muscle activity associated with each of the five primary milking tasks: pre-dipping, stripping, wiping, milk cluster attachment, and post-dipping. This study revealed that wiping and milk cluster attachment tasks required the most muscle activity. Identification of these two tasks as the most strenuous provides the groundwork for future researchers to explore different ergonomic intervention methods for milking tasks in addition to milk cluster attachment. The third study compared the sEMG associated with milking activities at large-herd operations with those in small-herd dairies. The results revealed that although work pace and total tasks completed per milking shift differed from one size of dairy to the other, milking work was strenuous in both cases. The comparison of muscle activity associated with small-herd and large-herd milking activities establishes that interventions to alleviate exposure to ergonomic risk factors may potentially be used interchangeably. Future research should continue to analyze differences between small and large-herd dairy operations by examining the specific milking tasks in both settings.